Implementation of a telehealth programme for patients with severe chronic obstructive pulmonary disease treated with long-term oxygen therapy - Jódar-Sánchez, Francisco; Ortega, Francisco; Parra, Carlos; Gómez-Suárez, Cristina; Jordán, Ana; Pérez, Pablo; Bonachela, Patricia; Leal, Sandra; Barrot, Emilia (SAGE Journals, 2013)
We conducted a pilot study of the effectiveness of home telehealth for patients with advanced chronic obstructive pulmonary disease treated with long-term oxygen therapy. Patients were randomized into a telehealth group (n=24) and a control group (n=21) who received usual care. Patients in the telehealth group measured their vital signs on weekdays and performed spirometry on two days per week. The data were transmitted automatically to a clinical call centre. After four months of monitoring the mean number of accident and emergency department visits in the telehealth group was slightly lower than in the control group (0.29 versus 0.43, p=0.25). The mean number of hospital admissions was 0.38 in the telehealth group and 0.14 in the control group (p=0.47). During the study a total of 40 alerts were detected. The clinical triage process detected eight clinical exacerbations which were escalated by the case manager for a specialist consultation. There were clinically important differences in health-related quality of life in both groups. The mean score on the SGRQ was 10.9 versus 4.5 in the control group (p=0.53). The EuroQol-5D score improved by 0.036 in the telehealth group and by 0.003 in the control group (p=0.68). Both patients and healthcare professionals showed a high level of satisfaction with the telehealth programme.
Keywords: Reconocimiento médico - Innovaciones tecnológicas; Evaluación económica; Telemedicina; EPOC